1992
DOI: 10.1007/bf02636335
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties for monitoring the quality of heated oils

Abstract: Dielectric properties (dielectric constant ~-' and dielectric loss E') were compared to conventional methods of analysis (viscosity, refractive index, iodine value, peroxide value and free fatty adds) for evaluating the frying quality of a blend of cottonseed and sunflower oils. The apparent relaxation time, T, the activation energy H and the entropy change S for dielectric relAxAtion of the heated oil samples were calculated. Results indicate that dielectric constant and dielectric loss are useful tools for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 6 publications
(6 reference statements)
0
19
0
1
Order By: Relevance
“…11. The dielectric constant of a vegetable oil blend of cottonseed and sunflower oil was reported to have increased by as much as 0.5 during the accelerated oxidation process [21]. It should be noted, however, that the impact of a change in the dielectric constant on the accuracy decreases for a decreasing film thickness.…”
Section: Resultsmentioning
confidence: 97%
“…11. The dielectric constant of a vegetable oil blend of cottonseed and sunflower oil was reported to have increased by as much as 0.5 during the accelerated oxidation process [21]. It should be noted, however, that the impact of a change in the dielectric constant on the accuracy decreases for a decreasing film thickness.…”
Section: Resultsmentioning
confidence: 97%
“…Simple and rapid methods for the detection of thermal abuse of oil are need of the hour. Many research works were carried out on dielectric properties of frying fats and oils (EI-Shaml et al 1992;Paul and Mittal 1996;Inoue et al 2002;Cataldo et al 2010). They reported that the dielectric constant is the most significant indicator for monitoring frying oil quality (quality control) in commercial deep fat frying operations.…”
Section: Food Grainsmentioning
confidence: 99%
“…Relation between TPC values and viscosity for oil was studied by early researchers and was observed that they were linearly correlated (Al-Kahtani 1991;El-Shami et al 1992). The maximum suggested levels for polar compounds present in frying or cooking fats and oil is 25/100 g of oil or 25 % (Pace et al 1968;Risman and Bengtsson 1971;El-Shami et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum suggested levels for polar compounds present in frying or cooking fats and oil is 25/100 g of oil or 25 % (Pace et al 1968;Risman and Bengtsson 1971;El-Shami et al 1992). Dillip Kumar et al (2013) have suggested that electrical properties may be used as indicators of condition and quality of edible oil.…”
Section: Introductionmentioning
confidence: 99%